Improved Quantification, Propagation, Purification and Storage of the Obligate Intracellular Human Pathogen Orientia tsutsugamushi. - Suparat Giengkam; Alex Blakes; Peemdej Utsahajit; Suwittra Chaemchuen; Sharanjeet Atwal; Stuart D Blacksell; Daniel H Paris; Nicholas P J Day; Jeanne Salje (Public Library of Science (PLoS), 2015)
BACKGROUND:Scrub typhus is a leading cause of serious febrile illness in rural Southeast Asia. The causative agent, Orientia tsutsugamushi, is an obligate intracellular bacterium that is transmitted to humans by the bite of a Leptotrombidium mite. Research into the basic mechanisms of cell biology and pathogenicity of O. tsutsugamushi has lagged behind that of other important human pathogens. One reason for this is that O. tsutsugamushi is an obligate intracellular bacterium that can only be cultured in mammalian cells and that requires specific methodologies for propagation and analysis. Here, we have performed a body of work designed to improve methods for quantification, propagation, purification and long-term storage of this important but neglected human pathogen. These results will be useful to other researchers working on O. tsutsugamushi and also other obligate intracellular pathogens such as those in the Rickettsiales and Chlamydiales families. METHODOLOGY:A clinical isolate of O. tsutsugamushi was grown in cultured mouse embryonic fibroblast (L929) cells. Bacterial growth was measured using an O. tsutsugamushi-specific qPCR assay. Conditions leading to improvements in viability and growth were monitored in terms of the effect on bacterial cell number after growth in cultured mammalian cells. KEY RESULTS:Development of a standardised growth assay to quantify bacterial replication and viability in vitro. Quantitative comparison of different DNA extraction methods. Quantification of the effect on growth of FBS concentration, daunorubicin supplementation, media composition, host cell confluence at infection and frequency of media replacement. Optimisation of bacterial purification including a comparison of host cell lysis methods, purification temperature, bacterial yield calculations and bacterial pelleting at different centrifugation speeds. Quantification of bacterial viability loss after long term storage and freezing under a range of conditions including different freezing buffers and different rates of freezing. CONCLUSIONS:Here we present a standardised method for comparing the viability of O. tsutsugamushi after purification, treatment and propagation under various conditions. Taken together, we present a body of data to support improved techniques for propagation, purification and storage of this organism. This data will be useful both for improving clinical isolation rates as well as performing in vitro cell biology experiments.